2009
DOI: 10.1007/s00213-009-1737-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment for eastward and westward travel preparation

Abstract: Appropriately timed 0.5 mg melatonin doses may avoid these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
(46 reference statements)
2
18
0
1
Order By: Relevance
“…This is somewhat better than the approximate 0.37 to 0.40 h advance we found with a single 60-min light pulse ). The combination of 3.0 mg melatonin and next morning light treatment gave a daily phase advance of about 0.87 h. This is similar to the net phase advance we recently achieved with 3 mg sustained release melatonin alone (Paul et al 2010) where sleep was also advanced and similar to the phase advance we report here in response to 3 mg SR alone.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is somewhat better than the approximate 0.37 to 0.40 h advance we found with a single 60-min light pulse ). The combination of 3.0 mg melatonin and next morning light treatment gave a daily phase advance of about 0.87 h. This is similar to the net phase advance we recently achieved with 3 mg sustained release melatonin alone (Paul et al 2010) where sleep was also advanced and similar to the phase advance we report here in response to 3 mg SR alone.…”
Section: Introductionsupporting
confidence: 87%
“…Subsequently, Revell et al demonstrated that the daily phase advance could be increased by about 20 min by adding afternoon melatonin in either 0.5 or 3.0 mg doses (Revell et al 2006). In a recent study, we compared the phase shifting efficacy of a single dose of each of three melatonin formulations; 3 mg regular release, 3 mg sustained release, and a surge-sustained release formulation (made up of 1 mg regular release and 2 mg sustained release) (Paul et al 2010). All three formulations created significant phase advances relative to placebo.…”
Section: Introductionmentioning
confidence: 96%
“…We have recently completed a 4-year project to evaluate, and provide a framework for, the manipulation of the circadian system forwards or backwards to minimize fatigue among Canadian Forces personnel during critical military operations [8][9][10]. This capability can be applied to help those military members who are posted in the high Arctic during the seasonal extremes of photoperiod (24 h darkness or 24 h sunlight) by providing the necessary circadian system time cues that are otherwise absent.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, light exposure should be managed in an adequate and timely fashion in order to allow (or avoid) the desired phase-changes. Also melatonin, a chronobiotic drug modulating SCN clock activity, can be used to advance the circadian phase (Paul et al 2010;Revell and Eastman 2005), induce daytime sleep (Rajaratnam et al 2004) or even synchronize circadian activity in blind subjects (reviewed in Skene and Arendt 2007). Chronic nocturnal work is the worse situation, since it involves uncontrolled nocturnal lighting exposure, forced arousal and nocturnal feeding, with a myriad of psychophysiological variables out of normal phase.…”
Section: Treatment Of Circadian Desynchronizationmentioning
confidence: 98%